2008
DOI: 10.1093/jpepsy/jsn121
|View full text |Cite
|
Sign up to set email alerts
|

Use of Handheld Wireless Technology for a Home-based Sickle Cell Pain Management Protocol

Abstract: Wireless data transfer technology has significant potential to become a practical method to improve symptom monitoring and communication between patients and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 26 publications
1
107
0
Order By: Relevance
“…Several studies in the surgical literature (14,15) have demonstrated the potential for "fast-tracking" postoperative patients with some success. Additionally, in patients with sickle-cell disease, a lot of research in emergency rooms and outpatient and inpatient settings has been focused on developing the best collaborative approach to minimize resource utilization and improve pain control (16)(17)(18). Another significant issue in IBD patients is nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the surgical literature (14,15) have demonstrated the potential for "fast-tracking" postoperative patients with some success. Additionally, in patients with sickle-cell disease, a lot of research in emergency rooms and outpatient and inpatient settings has been focused on developing the best collaborative approach to minimize resource utilization and improve pain control (16)(17)(18). Another significant issue in IBD patients is nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…11 One such application is the advanced symptom management system (ASyMS), developed to monitor and manage six symptoms (nausea, vomiting, mucositis, hand-foot syndrome, diarrhea, and fatigue) during treatment for lung, breast, or colorectal cancer among adult patients in the United Kingdom. 12 Software determined whether patient-reported symptoms required an immediate call from a healthcare professional or a self-care message tailored to the severity of their symptom.…”
Section: Introductionmentioning
confidence: 99%
“…One article (46) screened for persons with chronic (or recurrent) pain based on the American Psychological Association definition, and seven articles differentiated chronic from acute pain (27, 30, 41, 45) or were based on the number of vaso-occlusive crises (38, 41, 47). The remaining 20 articles did not mention if the intervention targeted acute pain, chronic pain, vaso-occlusive pain, or a combination.…”
Section: Resultsmentioning
confidence: 99%
“…After a thorough review of the non-pharmacological therapy literature for persons with SCD and chronic pain, we found only one article (46) that reported screening persons with chronic (or recurrent) pain based on the American Psychological Association definition of chronic pain. There were four additional articles that either defined or differentiated chronic (or recurrent) pain from acute pain or pain associated with vaso-occlusive crises (27,30,41, 45), and three studies that screened patients on the number of vaso-occlusive crises either within the last month (38) or year (41,47).…”
Section: Discussionmentioning
confidence: 99%